Structure-property relationship of reversible magnetic chirality tuning - Qi, Jing; Weber, Paula M.; Kißlinger, Tilman; Hammer, Lutz; Schneider, M. Alexander; Bode, Matthias (Physical Review B, 2023)
The Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction mediates collinear magnetic interactions via the conduction electrons of a nonmagnetic spacer, resulting in a ferro- or antiferromagnetic magnetization in magnetic multilayers. Recently it has been discovered that heavy nonmagnetic spacers are able to mediate an indirect magnetic coupling that is noncollinear and chiral. This Dzyaloshinskii-Moriya-enhanced RKKY interaction causes the emergence of a variety of interesting magnetic structures, such as skyrmions and spin spirals. Here, we show by spin-polarized scanning tunneling microscopy that the interchain coupling between manganese oxide chains on Ir(001) can reproducibly be switched from chiral to collinear antiferromagnetic by increasing the oxidation state of MnO2, while the reverse process can be induced by thermal reduction. The underlying structure-property relationship is revealed by low-energy electron diffraction intensity analysis. Density functional theory calculations suggest that the magnetic transition may be caused by a significant increase of the Heisenberg exchange which overrides the Dzyaloshinskii-Moriya interaction upon oxidation.
CRIS-Team Scopus Importer:2023-03-24